Analisis validitas bahan ajar bermuatan literasi saintifik pada materi kalor dan teori kinetik gas - Yuli Hafizah; Hidayati Hidayati; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2020)
The 21st century requires a person to read and write more (literacy) in order to improve one’s skills in thinking and acting. Supporting facilities for integrating literacy in the physics learning process can be by making teaching materials. Teaching material made is teaching material with scientific literacy in heat material and kinetic theory of gas. The purpose of the research that has been done is to determine the validity of teaching materials with scientific literacy in heat material and kinetic theory of gas. This type of research is Research and Development (R&D). The object of his research is teaching material with scientific literacy. The data collection instrument used was a validation test sheet to determine product validity. Validation was carried out by three experts namely physics lecturers at Universitas Negeri Padang. The validation test sheet consists of four assessment components, namely the suitability content, the presentation component, the linguistic component and the graphic component. The results of research that have been done, obtained teaching materials with scientific literacy in the theory of heat and kinetic gas which is valid. This means that teaching material with scientific literacy in the heat and kinetic theory of gas is valid to use.